Carbyne decorated porphyrins. Issue 35 (27th August 2020) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract : Porphyrins peripherally decorated with four transition-metal carbynes substituents are obtained in one step via a Pd 0 /Au I transmetallation shuttle beginning with a stannyl carbyne. Abstract : The Pd 0 /Au I -mediated coupling between stannylcarbyne [W(CSn n Bu3 )(CO)2 (Tp*)] (1 ) and meso -5, 10, 15, 20-tetrakis(3′ or 4′-bromophenyl)porphyrins gives tetrametallic derivatives where a central porphyrin unit is formally substituted at the four meso positions by tungsten benzylidyne moieties. These new 'metallo-porphyrins' undergo metallation at the porphyrin centres with Zn(OAc)2 ·2H2 O to give a pentametallic W4 Zn complex or at the tungsten–carbon triple bonds with [AuCl(SMe2 )] to give an octametallic W4 Au4 complex. The Zn(ii )-metalloporphyrin derivatives are capable of reversibly coordinating further axial ligands such as 4-dimethylaminopyridine or meta -pyridylcarbynes, which themselves are prepared via a coupling between 1 and the appropriate (di)bromopyridine.